CdS-sensitized 1-D single-crystalline anatase TiO2 nanowire arrays for photoelectrochemical hydrogen production. (5th January 2015) - Kim, Dong Hoe; Han, Hyun Soo; Cho, In Sun; Seong, Won Mo; Park, Ik Jae; Park, Jong Hoon; Shin, Sun; Park, Gyeong Do; Park, Sangbaek; Lee, Sangwook; Hong, Kug Sun
Abstract: We report photoelectrochemical (PEC) properties of single crystalline anatase TiO2 nanowire (NW) arrays which are sensitized with CdS for visible light activity. Photocurrent varies largely with increasing the growth time (from 2 to 24 h) of the TiO2 NWs and also increasing the deposition cycles (from 7 to 13 cycles) of CdS, which are attributed to changes in morphology of the TiO2 NWs and CdS layer. TiO2 NW array grown for 3 h with 9-cycles of CdS deposition exhibits the maximum photocurrent of 3.6 mA/cm 2 at 1.23 V vs. reversible hydrogen electrode (RHE) under the 1 SUN solar light. Morphological analysis combined with photoresponse analysis show that the 3 h-grown TiO2 NW array has the most suitable structure for PEC electrode because of large surface area for light absorption and chemical reaction, and that the 9-cycles deposited CdS layer provides the optimum light absorption and electron lifetime. Highlights: The PEC properties of 1-D anatase TiO2 NW/CdS electrodes are reported firstly. The effects of NW morphology and CdS cycles on properties of PEC were investigated. The 3 h growth NW shows vertically well-alignments and no canopy phase. The 9 CdS cycles has optimum condition for the charge generation and recombination. The 3 h growth NW with 9 CdS SILAR cycles shows the best performance.